FAKTOR-FAKTOR YANG MEMENGARUHI PRODUKSI USAHATANI CABAI MERAH KRITING DI DESA BULUPOUNTU JAYA KECAMATAN SIGI BIROMARU KABUPATEN SIGI - Gd. Wisnu Pranata; Lien Damayanti (Universitas Tadulako, 2016)
This study aimed to determine the effect of land use, fertilizer, seed and labor on the production of curly red chili in Bulupountu Jaya village Sigi Biromaru subdistrict of Sigi Regency. The population in this study was the whole group of 60 farmers who cultivate curly red chili within which a total sample of 37 farmer were selected to represent the population. Data obtained was analyzed using multiple linear analysis. Results of the analysis showed that the independent variables (X) simulataneously affect the production (the dependent variable, Y) significantly. This is showed by the value of the F-count of 63.528 whic is significant at 5% level. The value of the coefficient of determination (R2 ) was 0.969 indicating that 99% of the variation of the curly red chili production (Y) can be explained by such variables as land area (X1), urea (X2), ZA fertilizer (X3), ponska fertilizer (X4) seed (X5), pesticides (X6), and labor, (X7), while the other 1% can be explained other variables not including in the models. Land area, urea fertilizer, ZA fertilizer, ponska fertilizers, seeds, pesticides and labor simultaneously can affect the production of curly red chili farming in Bulupountu Jaya village sigiBiromarusubdistrictsigi Regency. Keywords: Production, Curly red chili, Bulupountu Jaya Village.